Competition, Imagery, and Pleasure in Plato’s Republic, 1–9 - Robinson, Matthew (PLATO JOURNAL, 2014)
This paper interprets the Republic’s “parallel” imagery of a contest between the lives of the most just and most unjust men as indicating that book 9’s two pleasure arguments are the culmination of the dialogue’s refutation of Thrasymachus’ sophistry. This strategic function of the pleasure arguments explains why Socrates designates the account of the just man’s pleasure the most severe defeat of the unjust man. The article concludes with a brief defense of using the contest imagery as an interpretive aid to the dialogue.